CASE STUDY: COMBINATION OF MINT INHALATION THERAPY AND BALLON BLOWING EXERCISE ON OXYGEN SATURATION AND BREATHING FREQUENCY IN CHILDREN'S PULMONARY TUBERCULOSIS - Innasa Permata Triaswidadi; Meivita Dewi Purnamasari (International Journal of Biomedical Nursing Review, 2026)
Introduction: Children aged < 5 years have a high risk of developing primary progressive pulmonary tuberculosis (TB) and are at risk of developing a serious disease that can cause death or long-term disability. Pulmonary TB is an infectious respiratory disease caused by the bacteria Mycobacterium tuberculosis. Objective: This case study aims to determine the effect of a combination of mint leaf inhalation therapy and balloon blowing exercise on oxygen saturation and respiratory frequency in children with pulmonary TB. Methods: : Implementation of Evidence Based Nursing (EBN) based on PICO with article searches for 2020 – 2024 using ScienceDirect, Pubmed, Research Gate and Google Scholar. A combination of mint leaf inhalation therapy and balloon blowing exercise was the intervention chosen to be implemented. The intervention was carried out by inhaling mint leaf essential oil vapor for 15 minutes and continued by blowing up the balloon 8 – 10 times until it was 7 inches in size. The intervention will be provided on April 18 – 24 2024. Results: After being given intervention, the oxygen saturation of the research subjects increased from 94% to 98% and the respiratory frequency decreased from 42x/minute to 36x/minute. Conclusion: The combination of pappermint inhalation therapy and balloon blowing exercise has an effect on increasing oxygen saturation and reducing respiratory frequency in children with pulmonary TB.